2007
DOI: 10.1021/ic070274o
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Ionic Crystals Assembled through Direct Incorporation of Polyoxometalate Clusters within 3D Metal−Organic Frameworks

Abstract: Polyoxometalate-based metal-organic frameworks {[Gd(dpdo)(4)(H(2)O)(3)](PMo(12)O(40))(H(2)O)(2)CH(3)CN}(n) (2), {[Dy(dpdo)(4)(H(2)O)(3)](PMo(12)O(40))(H(2)O)(20CH(3)CN}(n) (3), {[Gd(dpdo)(4)(H(2)O)(3)](H(3)O)(SiMo(12)O(40))(dpdo)(0.5)(CH(3)CN)(0.5) (H(2)O)(3)}(n) (4), {[Ho(dpdo)(4)(H(2)O)(3)](H(3)O)(SiMo(12)O(40))(dpdo)(0.5)(CH(3)CN)(0.5)(H(2)O)(3)}(n) (5), {[Ni(dpdo)(2)(CH(3)CN) (H(2)O)(2)](2)(SiMo(12)O(40))(H(2)O)(2)}(n) (6), and {[Ni(dpdo)(3)](4)(PW(12)O(40))(3)[H(H(2)O)(27)(CH(3)CN)(12)]}(n) (7) (where dpd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…More recently, it was reported that based on REDOR experiments acidic protons are localized on both bridging (O c ) and terminal (O d ) oxygen atoms of the Keggin unit in the anhydrous state of H 3 PW 12 O 40 [37]. In title complexes, there are 2.5 or 2 lattice water molecules and the separations between them are enough short to stabilize the excess proton to form some oligomer, so, we think that the excess proton is not localized on the surface of the polyanion [6][7][8]27].…”
Section: Structure Descriptionmentioning
confidence: 88%
See 3 more Smart Citations
“…More recently, it was reported that based on REDOR experiments acidic protons are localized on both bridging (O c ) and terminal (O d ) oxygen atoms of the Keggin unit in the anhydrous state of H 3 PW 12 O 40 [37]. In title complexes, there are 2.5 or 2 lattice water molecules and the separations between them are enough short to stabilize the excess proton to form some oligomer, so, we think that the excess proton is not localized on the surface of the polyanion [6][7][8]27].…”
Section: Structure Descriptionmentioning
confidence: 88%
“…These eight oxygen atoms are all crystallographically disordered, and this case can be found in many compounds [6][7][8]27]. The poly-Keggin-type anions play not only a chargecompensating role, but they can dramatically influence the overall solid-state architecture through their templating function, as well as the cationic framework with special channels also influences the polymerization of polyanions through its host function.…”
Section: Structure Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In title complex, there are three lattice water molecules and the separations between them are enough short to stabilize the excess proton to form such an oligomer as H 7 O 3 ? , so, we think that the excess proton is not localized on the surface of the polyanion [28][29][30][31][32][33].…”
Section: Measured Reflections 26764mentioning
confidence: 93%